23 MRI-conditionality has no impact on pacemaker and defibrillator lead parameter changes with MRI at 1.5 t. (May 2018) - Bhuva, Anish N; Lascelles, Karen; Patel, Kush; Lowe, Martin; Sekhri, Neha; Alpendurada, Francisco; Pennell, Dudley; Boubertakh, Redha; Schilling, Richard; Moon, James C; Baksi, AJohn; Manisty, Charlotte H
Abstract : Introduction: Although most pacemakers and defibrillators currently implanted are MRI-conditional, many still have legacy non-MRI conditional devices. Even following box-change to an MRI-conditional generator, these systems remain classed non-MRI conditional due to the leads, resulting in problems for patients accessing MRI. We therefore compared the effect of 1.5 T MRI on non-MRI conditional and MRI-conditional leads. Methods: Patients undergoing MRI for clinical indications in two centres over 2.5 years were included. Patients were scanned at 1.5 T according to institutional protocols, with devices interrogated pre- and post-scan, and complications recorded. Analysis of changes to lead parameters peri-scan were stratified by MRI-conditionality and presented as mean (95% confidence interval). Results: 201 MRI examinations (64% cardiac) were performed with no clinical complications in 185 patients (75 with defibrillators, 60 pacemaker-dependent). Of 442 leads scanned, 152 (34%) were non-conditional. Overall following MRI, although atrial lead amplitude reduced by 0.17 (0.05, 0.35) mV (p=0.008) with small statistically significant changes to lead impedance, pacing thresholds were unchanged. There were no significant differences in changes peri-scan between MRI-conditional and non-MRI conditional leads, including defibrillator leads (p=NS for all parameters). Parameter changes exceeding pre-specified cut-offs occurred in 25% of MRI-conditional and 21% non-MRI conditional leads. There was no influence of generator or lead age, or thoracic imaging on lead parameter changes. Discussion: This study suggests the risk of scanning non-MRI conditional leads is no greater than with MRI-conditional leads. Larger studies are warranted to assess whether patients with MRI-conditional generators but non-MRI conditional leads should be re-stratified as 'MRI-conditional'.